Rethinking the neoliberal university: embracing vulnerability in English law schools?. Issue 1 (2nd January 2021) - Morrison, Doug; Guth, Jessica
ABSTRACT: This paper draws on our continuing work on the neoliberal and marketised law school and seeks to understand how we might apply vulnerability theory to address some of the problems resulting from current higher education and law school contexts. After outlining our understanding of vulnerability theory and summarising what we believe are some of the ills of a neoliberal law school, this paper argues that vulnerability theory allows us to reframe our thinking about academic labour and law schools on a theoretical level. As such it is useful for a longer-term project which seeks to challenge existing structures. For more immediate concerns however, the paper suggests, vulnerability theory is less useful because it does not yet provide tools which can be easily operationalised to make a significant difference in our everyday academic lives.